PENDEKATAN KEPEMIMPINAN DALAM PEMBERDAYAAN MANAJEMAN SUMBER DAYA MANUSIA DI PRODUCTION HOUSE (Studi Kasus Pada PT. Samuan Rumah Kreasi) - . Fitriyanto (Universitas Bina Sarana Informatika, 2017)
In this research is done in order to know the approach of leadership of management in empowering the employee and the claim of creative industrial sector in this matter the company of production house that have a business in television program production, film, advertisement and Company Profile. In this research the writer want to point out whereas the management party or the leader of production house want the better approach in order to empowering the human resource that be owned in order that can fulfill the needs of company and the needs or claim of customer but often have an obstacle by the claim of job or deadline of production such as; the job hour of employee and the claim of production, the development of technology and other factor. How about the approach of leader in this matter is management of a production house in creating the target of company through the empowerment of their human resources by various of policy which have been implemented well is protection, empowering, enabling, and supporting.Keywords: Leadership, MSDM Empowerment, Production House